Pointwise Fourier Inversion of Distributions on Projective Spaces - Vieli, Francisco Javier Gonz´alez (Sarajevo Journal of Mathematics, 2022)
Given a distribution T on the real, complex or quaternionic projective space we define, in analogy to the work of Łojasiewicz, the value of T at a point z of the projective space and we show that, if T has the value τ at z, then the Fourier-Laplace series of T at z is Abel-summable to τ.